Preventable Emergency Department Visits After Colorectal Surgery. Issue 11 (24th June 2021) - Wong, Daniel J.; Roth, Eve M.; Sokas, Claire M.; Pastrana Del Valle, Jonathan R.; Fleishman, Aaron; Gaytan Fuentes, Israel A.; Storino, Alessandra; Fakler, Michelle N.; Fabrizio, Anne C.; Cataldo, Thomas E.; Messaris, Evangelos
Abstract : Supplemental Digital Content is available in the text. Abstract : BACKGROUND: The emergency department plays a common and critical role in the treatment of postoperative patients. However, many quality improvement databases fail to record these interactions. As such, our understanding of the prevalence and etiology of postoperative emergency department visits in contemporary colorectal surgery is limited. Visits with potentially preventable etiologies represent a significant target for quality improvement, particularly in the current era of rapidly evolving postoperative and ambulatory care patterns. OBJECTIVE: We aimed to characterize postoperative emergency department visits and identify factors associated with these visits for potential intervention. DESIGN: This was a retrospective cohort study. SETTINGS: The study was conducted at an academic medical center. PATIENTS: Consecutive patients undergoing colectomy or proctectomy within the division of colorectal surgery at an academic medical center between 2014 and 2018 were included. MAIN OUTCOME MEASURES: Frequency and indication for emergency department visits, as well as clinical and sociodemographic factors associated with emergency department visits in the postoperative period, were included measures. RESULTS: From the 1763 individual operations, there were 207 emergency department visits from 199 patients (11%) within 30 days of discharge. Two thirds of emergency department visits led to readmission. Median (interquartile range) time to presentation was 8 days (4–16 d). Median time in the emergency department was 7.8 hours (6.0–10.1 h). One third of visits were identified as potentially preventable, most commonly for pain (17%) and stoma complications (excluding dehydration; 13%). A primary language other than English was associated with any postoperative emergency department visit risk ratio of 2.7 (95% CI, 1.3–5.3), as well as a preventable visit risk ratio of 3.6 (95% CI, 1.7–8.0). LIMITATIONS: This was a single-center study and a retrospective review. CONCLUSIONS: One third of emergency department visits after colorectal surgery are potentially preventable. Special attention should be directed toward those patients who do not speak English as a primary language. See Video Abstract at http://links.lww.com/DCR/B648 . SE PUEDEN EVITAR LAS VISITAS AL SERVICIO DE URGENCIA DESPUÉS DE UNA CIRUGÍA COLORECTAL?: ANTECEDENTES: Las unidades de emergencia tienen un rol fundamental en el periodo posterior a una cirugía. Sin embargo muchos de los registros en las bases de datos de estas secciones no son de buena calidad. Por esto analizar la prevalencia y etiología de las visitas postoperatorias en cirugía colorectal resulta ser bastante limitada. Para lograr una mejoría en la calidad es fundamental analizar las causas potencialmente evitables, especialmente al considerer la rapida evolucion de los parametros de medición actuales. OBJETIVO: Nuestro objetivo es caracterizar las visitas postoperatorias al servicio de urgencias e identificar los factores asociados potencialmente evitables. DISEÑO: Estudio de cohorte retrospectivo. AJUSTE: Centro médico académico, 2014-2018. PACIENTES: Pacientes consecutivos sometidos a colectomía o proctectomía dentro de la división de cirugía colorrectal en un centro médico académico entre 2014 y 2018. PRINCIPALES MEDIDAS DE RESULTADO: Frecuencia e indicación de las visitas al servicio de urgencias en el period postoperatorio: factores clínicos y sociodemográficos. RESULTADOS: De 1763 operaciones individuales, hubo 207 visitas al departamento de emergencias de 199 pacientes (11%) en los 30 días posteriores al alta. Dos tercios de las visitas al servicio de urgencias dieron lugar a readmisiones. La mediana [rango intercuartílico] de tiempo hasta la presentación fue de 8 [4-16] días. La mediana de tiempo en el servicio de urgencias fue de 7, 8 [6-10, 1] horas. Un tercio de las visitas se identificaron como potencialmente evitables, más comúnmente dolor (17%) y complicaciones del estoma (excluida la deshidratación) (13%). En los pacientes con poco manejo del inglés se asoció con una mayor frecuencia razón de visitas al departamento de emergencias posoperatorias [IC del 95%] 2, 7 [1, 3-5, 3], así como opetancialmente evitables con un RR de 3, 6 [1, 7-8, 0]. LIMITACIONES: Estudio de un solo centro y revisión retrospectiva. CONCLUSIÓN: Al menos un tercio de las visitas al servicio de urgencias después de una cirugía colorrectal son potencialmente evitables. Se debe prestar especial atención a los pacientes que no hablan inglés como idioma materno. Consulte Video Resumen en http://links.lww.com/DCR/B648 .